Application of the Problem Based Learning (PBL) Assisted by Powtoon Video Media on Student Learning Activities and Outcomes on Periodic System of Elements Material - Aryani, widya; Pulungan, Ahmad Nasir (Universitas Lampung, 2024)
Application of the Problem Based Learning (PBL) Assited by Powtoon Video Media on Student learning Activities and Outcomes on Periodic System of Elements Material. This research aims to (1) Knowing that the learning outcomes and learning activities of students who are taught with the help of PowerPoint animation video media are higher than the chemistry learning outcomes of students who are taught with the help of PowerPoint media. (2) Knowing that there is a correlation between activities and student learning outcomes.The research population was all class X high school studentsDHARMAWANGSA MEDAN consists of 9 classes, with a purposive sampling method. The results obtained are in (1) The learning results using the right-hand t test obtained tcount > ttable = 3.61 > 1.67, so the learning outcomes of students taught using the PBL model assisted by Powtoon Video Media are higher than the learning outcomes of students taught with the PBL model assisted by Powerpoint Media. (2) Learning activity data shows that the value of tcount > ttable = 1.80 > 1.67, so the learning activities of students taught using the PBL model assisted by Powtoon Video Media are higher than the learning outcomes of students taught using the PBL model assisted by Powerpoint Media in Periodic System of Elements material, (3) the results of the correlation test show that the value of rcount > rtable = 0.73 > 0.36, meaning there is a significant correlation between activities and student learning outcomes taught using the PBL model assisted by Powtoon Video Media in the Periodic System material Element with a coefficient of determination of 54%.Keywords: Problem Based Learning, Powtoon, Learning Outcomes, Learning Activities,Periodic System Of ElementsDOI: 10.23960/jppk.v13.i1.2024.15